Distinct Ultrasound Features of Giant Solitary Fibrous Tumour of the Pleura: A Case Report - Charles Wong; Chun‐Kei Cheung; Hei‐Shun Cheng; Pui‐Hing Chiu; Chun‐Wai Tong; Flora Pui‐Ling Miu (Respirology Case Reports, 2025)
ABSTRACT Solitary fibrous tumour of the pleura (SFTP) accounts for < 5% of pleural tumours, and the ultrasound (US) features of giant SFTP (> 20 cm) remain unknown. We present the case of a woman diagnosed with giant SFTP associated with Doege–Potter syndrome, who experienced dyspnea and recurrent hypoglycemia. Chest x‐ray revealed a large left hemithorax opacity, initially misdiagnosed as massive pleural effusion, leading to an inappropriate thoracentesis. Subsequent US demonstrated a large heterogeneous mass with intralesional cystic changes and calcifications, which lacks respiratory movement. Computed tomography showed a 27 cm × 15 cm × 12 cm left pleural mass. US‐guided biopsy confirmed SFTP. Complete surgical resection resolved all symptoms, including hypoglycemia. This case highlights the distinct US features of giant SFTP, which differ from smaller SFTP reported in the literature. Awareness of the variable US characteristics of SFTP across different sizes can enhance accurate diagnosis and facilitate management.